Peranan Kajian Remaja Masjid Al-Huda dalam Meningkatkan Kesadaran Beragama Remaja di Desa Hutana Godang Kabupaten Pasaman Barat - Warzukni, Warzukni; Satria, Rengga (Lembaga Yasin AlSys, 2024)
This research aims to find out what are the programs of mosque youth, how the participation of mosque youth and the role of mosque youth studies in increasing the religious awareness of adolescents in Hutana Godang Village, West Pasaman Regency. The method used in this research is descriptive qualitative, while the type of research used is qualitative research. The research time was carried out on September 23 to October 23, 2024 in Hutana Godang Village, West Pasaman Regency. The data sources in this study are the chairman of the youth mosque and the youth mosque Al-Huda Hutana Godang. Data collection was carried out using observation, interview, and documentation methods. The data that has been collected is then analyzed by data reduction, data presentation, and conclusion drawing. Data validation in this study uses source triangulation, in which researchers compare data or information obtained in the field and then re-correct data or information that has been collected from various sources related to the role of the study of al-huda mosque teenagers in increasing teenagers' religious awareness. The results showed that the role of the al-huda mosque youth study in increasing the religious awareness of adolescents in Hutana Godang Village, West Pasaman Regency was quite good in its implementation as seen from several al-huda mosque youth programs, namely routine recitation, studies that are held regularly provide opportunities for adolescents to explore Islamic teachings, both in terms of creed, Second, social religious activities such as helping the community in religious events, working together to clean the mosque, and social services, Third, celebrating Islamic holidays such as maulid nabi and isra' mi'raj, the involvement of mosque youth in this commemoration has a positive impact on developing their organizational skills and responsibilities. The participation of mosque teenagers in increasing the religious awareness of teenagers shows that although many are active in social activities, there are still a number of teenagers who do not participate in religious studies. The role of mosque youth studies in increasing adolescents' religious awareness is as a means to form good character by learning about the importance of worship, good morals, and concern for others, adolescents can understand their responsibilities as religious individuals.